Manual Archiving System: How Its Impact on Hospital Service? - Ilmi, Hanifah Mufidatul; Awalin, Alvinda Rizka; Panduwinata, Lifa Farida (Universitas Negeri Surabaya, 2024)
This study aims to determine the effectiveness of archive management in the secretariat section of Hospital X in Sidoarjo. This study used a qualitative method with a case study approach. Data were collected using observation, documentation and unstructured interviews. The result of the study shows that the management of archives using a manual system atHospital X in the Sidoarjo area is not yet effective. Despite employees having job satisfaction and a high sense of responsibility, the hospital has not consistently achieved 100% target fulfilment. Various obstacles continue to hinder effective archival management